2020
DOI: 10.1111/jace.17417
|View full text |Cite
|
Sign up to set email alerts
|

Piezo/pyro/photo‐catalysis activities in Ba0.85Ca0.15(Ti0.9Zr0.1)1‐xFexO3 ceramics

Abstract: Ba 0.85 Ca 0.15 (Ti 0.9 Zr 0.1) 1-x Fe x O 3 (x = 0, 0.5, and 1%) ceramics were studied for piezocatalysis, photocatalysis, and pyrocatalysis using dye degradation in the simulated wastewater. The effect of electrical poling was also performed and found a significant impact of poling on all three catalytic reactions. Fe decreased the optical bandgap of Ba 0.85 Ca 0.15 Ti 0.9 Zr 0.1 O 3 (BCZTO) to the visible region. Bandgap for x = 0, 0.005, and 0.01 was found to be 3.14 eV, 2.75 eV, and 2.61 eV, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…The high interfacial energy at MPB can drive the coupling between the local polar defect heterogeneities and ferroelectric polarization, leading to defect‐induced gap‐states whilst maintaining high piezoelectricity (Figure 9d). [ 35,91–94 ] Sharma and Vaish [ 95 ] reported a bandgap engineered Ba 0.85 Ca 0.15 (Ti 0.9 Zr 0.1 ) 1‐ x Fe x O 3 ceramic with a low bandgap of 2.61 eV, and achieved piezo/pyro/photocatalytic activities, which validates the triple‐state multiple catalysts behavior of ferroelectric materials.…”
Section: Defect and Microstructure Engineeringmentioning
confidence: 77%
See 2 more Smart Citations
“…The high interfacial energy at MPB can drive the coupling between the local polar defect heterogeneities and ferroelectric polarization, leading to defect‐induced gap‐states whilst maintaining high piezoelectricity (Figure 9d). [ 35,91–94 ] Sharma and Vaish [ 95 ] reported a bandgap engineered Ba 0.85 Ca 0.15 (Ti 0.9 Zr 0.1 ) 1‐ x Fe x O 3 ceramic with a low bandgap of 2.61 eV, and achieved piezo/pyro/photocatalytic activities, which validates the triple‐state multiple catalysts behavior of ferroelectric materials.…”
Section: Defect and Microstructure Engineeringmentioning
confidence: 77%
“…[ 117 ] Compared with microscale KN‐BNZ particles, the research on the catalytic performance of the nanoscale particles is highly expected. Sharma and Vaish [ 95 ] successfully prepared Fe doped Ba 0.85 Ca 0.15 (Ti 0.9 Zr0.1) 1‐ x Fe x O 3 and engineered the bandgap from 3.14 to 2.61 eV via SSR. Though Fe doping can induce substantial piezo/pyro/photocatalytic activities, the ceramic form has greatly limited the multicatalytic performance due to its small surface area.…”
Section: Progress In Synthesis and Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic working principle of pyro-catalysis is similar to that of photo-catalysis and piezo-catalysis, i.e., generation of ROS in response to the external stimuli, but the stimuli of pyro-catalysts are temperature fluctuations, rather than the light or mechanical vibration for photo- and piezo-catalysts. Although the pyro-catalysis and photo-catalysis exhibit the same electrochemical-redox process 29 31 , the pyro-catalysis has drawn less technological attention relative to photo-catalysis due to its power-based temperature fluctuation stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Most of the recent studies have reported piezocatalysis using BaTiO 3 , Sr 0.7 Ba 0.3 Nb 2 O 6 , Bi 4 Ti 3 O 12 , LiNbO 3 , K 0.5 Na 0.5 NbO 3 , Bi 0.5 Na 0.5 TiO 3, Pb(Zr,Ti)O 3 , Ba 0.85 Ca 0.85 Ti 0.90 Zr 0.10 O 3 (BCZTO), and ZnO. [13][14][15][16][17][18][19][20][21] Among these, BaTiO 3 is the simplest, traditional, and important ferroelctric ceramics. It has been well explored for various physical and chemical modifications.…”
Section: Introductionmentioning
confidence: 99%